2017
DOI: 10.3389/fncir.2017.00061
|View full text |Cite
|
Sign up to set email alerts
|

Linking Network Activity to Synaptic Plasticity during Sleep: Hypotheses and Recent Data

Abstract: Research findings over the past two decades have supported a link between sleep states and synaptic plasticity. Numerous mechanistic hypotheses have been put forth to explain this relationship. For example, multiple studies have shown structural alterations to synapses (including changes in synaptic volume, spine density, and receptor composition) indicative of synaptic weakening after a period of sleep. Direct measures of neuronal activity and synaptic strength support the idea that a period of sleep can redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(136 citation statements)
references
References 164 publications
(227 reference statements)
7
128
0
1
Order By: Relevance
“…Thus, about 20% of synapses or synaptic activity may be lost during sleep. Although the molecular and cellular mechanisms have not been well understood (Puentes-Mestril & Aton, 2017), this study presents a series of evidence supporting that microglial cells eliminate synapses through phagocytosis during sleep.…”
Section: Phagocytic Elimination Of Synapses By Microgliamentioning
confidence: 79%
“…Thus, about 20% of synapses or synaptic activity may be lost during sleep. Although the molecular and cellular mechanisms have not been well understood (Puentes-Mestril & Aton, 2017), this study presents a series of evidence supporting that microglial cells eliminate synapses through phagocytosis during sleep.…”
Section: Phagocytic Elimination Of Synapses By Microgliamentioning
confidence: 79%
“…The synaptic homeostasis hypothesis (SHY) proposes that wakefulness drives learning-related increases in synaptic strengths and FRs, while sleep renormalizes activity by down-regulating synaptic strengths, a process dependent on activity patterns during NREM sleep (Tononi and Cirelli, 2014). A combination of structural, electrophysiological and molecular evidence has been put forward in support of SHY (de Vivo et al, 2017;Vyazovskiy et al, 2008;Vyazovskiy et al, 2009;Liu et al, 2010;Diering et al, 2017), but contradictory data have also been reported (Yang et al, 2014;Chauvette et al, 2012;Aton et al, 2014;Durkin and Aton, 2016), and in some cases the interpretation of these findings has been questioned (Frank, 2012;Frank and Cantera, 2014;Timofeev and Chauvette, 2017;Puentes-Mestril and Aton, 2017). In particular, it has been unclear whether sleep and wake cause global oscillations in firing rates under baseline conditions, when animals have not experienced a dramatic plasticity or learning event.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for the link between increased genioglossus memory and SWS are still largely unknown. Most of the previous literature related to the effects of SWS on synaptic plasticity investigated forebrain mechanisms, which probably cannot be translated to the brainstem given the deeply different networks in which these circuits are embedded (Huber et al 2004;Chauvette et al 2012;Puentes-Mestril & Aton, 2017).…”
Section: Example Of Ventilatory Drive Tonic and Phasic Genioglossumentioning
confidence: 99%
“…Other causes are related to circuit mechanisms involving feedback loops and changes in the balance of inhibitory and excitatory inputs (Zucker & Regehr, ; Tadjalli et al . ; Puentes‐Mestril & Aton, ). These various mechanisms may play a role in the development of stable breathing during SWS by increasing genioglossus activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation